Peran Baitut Tamwil Muhammadiyah (BTM) Taqwa Dalam Peningkatan Ekonomi Mikro Syariah Di Kecamatan Singkut Kabupaten Sarolangun Provinsi Jambi - Saipullah Hismaslul; Usdeldi Usdeldi; Sucipto Sucipto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research examines Baitut Tamwil Muhammadiyah (BTM) Taqwa in improving sharia microeconomics in Singkut sub-district, Sarolangun district, Jambi province. The aim of the research is to find out the strategic role of BTM Taqwa in improving sharia microeconomics. Apart from that, to find out the supporting and inhibiting factors experienced by BTM taqwa. This type of research is qualitative using a managerial and sharia economic approach; the research paradigm is direct involvement and intense interaction with informants; data sources are empirical data obtained in the field through the Founding Board, Management, Members and customers of BTM Taqwa as well as the regional government of Singkut sub-district, Sarolangun district, Jambi province (primary sources) and documents and books related to research (secondary data); The instruments for this research are observation, interviews and documentation and the data collection tools are observation guides, interview guides and documentary study guides; data collection stages include preparation, implementation and preparation; and the validity testing techniques used are credibility and compatibility. The results of this research show that BTM Taqwa plays a role in improving sharia microeconomics in Singkut sub-district, Sarolangun Regency, Jambi Province. The role played by BTM Taqwa is the role of empowering human resources and an entrepreneurial spirit, the role of improving microeconomic welfare, and the role of distancing people from the practice of usury. The results of this research also show that the supporting factors for BTM Taqwa's success in micro economics internally are strategic location, commitment of the board of trustees, management and members, and high participation in member savings, while externally there is high demand from micro business actors for BTM Taqwa, ease of obtaining business capital assistance received by micro business actors, and government support. The inhibiting factors experienced by BTM taqwa internally are BTM taqwa's lack of human resources, lack of financial capital and technology, while externally there are many customers who are lazy about making savings capital payments.